Engineering Turbulence Modelling and Experiments 5 2002
DOI: 10.1016/b978-008044114-6/50016-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of Generalized Wall Function for Complex Turbulent Flows

Abstract: Abstract. This paper describes a generalized wall function for threedimensional turbulent boundary layer flows. Since the formulation is valid for various pressure gradients including those associated with zero skin friction, it can be applied to wall bounded complex flows with acceleration, deceleration and recirculation. This generalized wall function is extended to the whole surface layer (or inner layer), covering the viscous sublayer, buffer layer and inertial sublayer; therefore, it is a unified wall fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 4 publications
(4 reference statements)
0
23
0
Order By: Relevance
“…Adverse gradients are created by cross-flows [38], and, importantly, interact strongly with the local flows behind cylinders. Very recently Shih et al [39] have developed a generalised wall function, for both types of pressure gradient. Alternatively, some codes (e.g.…”
Section: Predictions Using a Proprietary Cfd Packagementioning
confidence: 99%
“…Adverse gradients are created by cross-flows [38], and, importantly, interact strongly with the local flows behind cylinders. Very recently Shih et al [39] have developed a generalised wall function, for both types of pressure gradient. Alternatively, some codes (e.g.…”
Section: Predictions Using a Proprietary Cfd Packagementioning
confidence: 99%
“…This approach showed good performance in several boundary layer flows including transonic, supersonic and hypersonic flows. More recently, Shih et al (2003) employed a combined velocity scale composed of a friction velocity and a pressure gradient. Although the logarithmic velocity distribution was still used, they obtained successful results for flows with a separation and an adverse pressure gradient according to the use of the combined velocity scale.…”
Section: Introductionmentioning
confidence: 99%
“…A previous experience in the RANS simulation showed that the generalized wall function was able to catch the near wall behavior of turbulent mean profile toward the wall. However, the RANS without wall function needs a fine grid resolution near the wall (see [10]). In our PRNS simulation of NACA0012 airfoil, the grid near the wall is quite fine.…”
Section: About Near Wall Turbulencementioning
confidence: 99%
“…Here we just report what we have found so far for the wall bounded internal and external flows. In the internal flow simulations using NCC code (see [1] and the present paper), a generalized wall function [10] was used to avoid the immediate vicinity of the wall (as a common practice in LES type of simulations). In our previous PRNS simulation of pipe flows at different Reynolds numbers, the results with RCP=0.38 were well compared with the available experimental data from the center line all the way toward the wall.…”
Section: About Near Wall Turbulencementioning
confidence: 99%
See 1 more Smart Citation